The birch reduction of 3-substituted pyrroles - Donohoe, T; Guyo, P; Harji, R; Helliwell, M; Cousins, R (1998)
The Birch reduction of electron-deficient 3-substituted pyrroles is described. Use of a reductive alkylation procedure involving sodium metal in liquid ammonia gave good yields of 4-alkyl-2-pyrrolines. The identity of these products was proven by an X-ray structure of a crystalline derivative. Moreover, the pyrroles used in this study could be readily prepared by reaction of TOSMIC with acrylic amides and esters and, once the reduction was complete, the ester activating group could be easily removed to yield the corresponding N-protected β-proline derivatives.